Financial reporting transparency, citizens' understanding, and public participation: A survey experiment study - Langella C; Anessi-Pessina E; Botica Redmayne N; Sicilia M (John Wiley and Sons Ltd, 2023)
This study investigates the conditions under which transparency contributes to citizens' understanding of financial reporting and examines how this enhanced understanding is associated with public participation. To this end, a survey experiment was conducted in which two attributes of financial reporting transparency (i.e., content clarification and presentation format) were the manipulated variables, whereas citizens' understanding and public participation were the outcome variables. Results demonstrate that the provision of explanations to clarify obscure technical jargon does have a positive effect on citizens' understanding. A similar effect was found for the provision of graphical and visual representations. However, the study reveals that there is no additional benefit in simultaneously providing both explanations of technical jargon and visual aids. Furthermore, findings show that the levels of public participation are highest among the individuals who felt they understood the financial information the best, but yet possessed the lowest level of actual understanding.